PSIKOTIK DAN PEDOFILIA DALAM “MAK IPAH DAN BUNGA-BUNGA” KARYA INTAN PARAMADHITA: KAJIAN PSIKOLOGI SASTRA - Choirunnisa Salwa Tawakal (Mahakarya: Jurnal Mahasiswa Ilmu Budaya, 2022)
This study aimed at describing mental disorders (psychic) ​​experienced by two characters, Mak Ipah and Pemuda in “Mak Ipah dan Bunga-bunga” written by Intan Paramadhita. The two characters (protagonist and antagonist) of the short story were analyzed using psychoanalysis theory. The theory believes that human being is more influenced by the subconscious than the conscious. Like a psychotic patient with schizophrenia; the patient is unaware of his deviant behavior or pedophilia and only cares about his desire (affecting his sexual behavior) for children, which he considers as something natural. This study used qualitative-descriptive method. The research data were in the form of literary text (short story) that represents a person's mental disorder (the characters). The sources of resesarch data were from the narrative text of the short story "Mak Ipah dan Bunga-bunga" by Intan Paramadhita. The results showed that after the death of his only child, Mak Ipah was considered an insane individual and was then singled out by all the villagers. She became apathetic and chose to interact with the plants in her yard because she forgot the people around her. From this, the hypothesis drawn was that Mak Ipah has a psychological disorder, namely a psychotic type of schizophrenia due to a past trauma. Meanwhile, the other character named Pemuda suffered from a psychological disorder, namely pedophilia. It can be concluded that this short story tells two abnormal characters, and proves that "Mak Ipah and Bunga-bunga" is a short story with psychological disorders in its narration.